Eradicating xenophobia and aporophobia: Compassion as a key capacity of moral neuroeducation - Javier Gracia Calandín (Universidad Pontificia Comillas, 2021)
Drawing on the contributions of some of the most recent and relevant studies on neuroethics and moral neuroeducation, this paper undertakes an analysis of compassion. In order to focus on the results of this neuroscientific research a reductionist naturalist framework is set aside in order to embrace the broader outlook of a moral neuroeducation that, firstly, refuses to reduce its normative character to the human capacity for evolutionary adaptation; and, secondly, seeks to locate within the brain the neuronal foundations for the development of a capacity for compassion towards those of one’s own community, and also those from outside it. Thereby, this capacity for compassion moves beyond empathic tribalism.